Formulation and In Vitro Evaluation of Pulsatile Drug Delivery System of Ketoprofen - Borse, Rahul D.; Derle, Deelip V.; Datta, Saptarshi (Asian Journal of Pharmaceutical Research and Development, 2013)
In this study, investigation of pulsatile drug delivery system to achieve time and site specific release of Ketoprofen, based on chronopharmaceutical consideration. The rapid release core tablet contained drug Ketoprofen and superdisintegrant Sodium Starch Glycolate or Croscarmellose and a coating material Eudragit S100. The core tablets of Ketoprofen were prepared by direct compression method with superdisintegrants and other excipients. The pulsatile tablets prepared by using Eudragit S 100 in concentration of 1%, 2% and 3% coating solution. The formulated pulsatile tablets were evaluated for weight variation, hardness, % friability, % drug content and in-vitro drug release. The in-vitro drug release were carried out using pH 1.2 for first 2 hrs, then in pH 6.8 for 4 hrs and in pH 7.4 for period upto 8 hrs. At the end of 8 hr the drug release were 98.34±0.27, 96.44±0.41 and 95.84±0.23 in 1%, 2% and 3% respectively. From obtained results it was found that 1% coating of Eudragit S 100 showed more release than other concentration. The developed formulations showed uniform appearance, average weight, drug content and adequate hardness. It can be concluded from present research the optimized batch (1% Coating batch) beneficial for the pulsatile drug delivery system.